The human anti‐HIV antibodies 2F5, 2G12, and PG9 differ in their susceptibility to proteolytic degradation: Down‐regulation of endogenous serine and cysteine proteinase activities could improve antibody production in plant‐based expression platforms. Issue 4 (April 2014) - Niemer, Melanie; Mehofer, Ulrich; Torres Acosta, Juan Antonio; Verdianz, Maria; Henkel, Theresa; Loos, Andreas; Strasser, Richard; Maresch, Daniel; Rademacher, Thomas; Steinkellner, Herta; Mach, Lukas
Abstract The tobacco‐related species Nicotiana benthamiana has recently emerged as a promising host for the manufacturing of protein therapeutics. However, the production of recombinant proteins in N. benthamiana is frequently hampered by undesired proteolysis. Here, we show that the expression of the human anti‐HIV antibodies 2F5, 2G12, and PG9 in N. benthamiana leaves leads to the accumulation of discrete heavy chain‐derived degradation products of 30–40 kDa. Incubation of purified 2F5 with N. benthamiana intercellular fluid resulted in rapid conversion into the 40‐kDa fragment, whereas 2G12 proved largely resistant to degradation. Such a differential susceptibility to proteolytic attack was also observed when these two antibodies were exposed to various types of proteinases in vitro. While serine and cysteine proteinases are both capable of generating the 40‐kDa 2F5 fragment, the 30‐kDa polypeptide is most readily obtained by treatment with the latter class of enzymes. The principal cleavage sites reside within the antigen‐binding domain, the VH–CH1 linker segment and the hinge region of the antibodies. Collectively, these results indicate that down‐regulation of endogenous serine and cysteine proteinase activities could be used to improve the performance of plant‐based expression platforms destined for the production of biopharmaceuticals.